2019
DOI: 10.1103/physrevlett.123.206403
|View full text |Cite
|
Sign up to set email alerts
|

Rigid Band Shifts in Two-Dimensional Semiconductors through External Dielectric Screening

Abstract: We investigate the effects of environmental dielectric screening on the electronic dispersion and the band gap in the atomically-thin, quasi two-dimensional (2D) semiconductor WS2 using correlative angle-resolved photoemission and optical spectroscopies, along with first-principles calculations. We find the main effect of increased environmental screening to be a reduction of the band gap, with little change to the electronic dispersion of the band structure. These essentially rigid shifts of the bands results… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(110 citation statements)
references
References 30 publications
(38 reference statements)
10
100
0
Order By: Relevance
“…The displayed fits yield A = 45 +1 −2 meV/ε%, E I (0) = 2.13 +0.07 −0.04 eV and I = 92 +17 −9 meV/ε% [E A (0) is fixed to 2.00 eV, the strain-free ML exciton energy]. These data compare rather favorably with the experimental [35,45], and theoretical [17,18,[20][21][22][24][25][26][27]46] ones as reported in Table I. However, we notice a large discrepancy between the E I (0)-E A (0) value derived in this work (130 meV) and those reported in other works.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…The displayed fits yield A = 45 +1 −2 meV/ε%, E I (0) = 2.13 +0.07 −0.04 eV and I = 92 +17 −9 meV/ε% [E A (0) is fixed to 2.00 eV, the strain-free ML exciton energy]. These data compare rather favorably with the experimental [35,45], and theoretical [17,18,[20][21][22][24][25][26][27]46] ones as reported in Table I. However, we notice a large discrepancy between the E I (0)-E A (0) value derived in this work (130 meV) and those reported in other works.…”
supporting
confidence: 56%
“…1.8 ± 0.7 0.1 [5,17,[19][20][21][23][24][25]27,32] data embed exciton effects that are quite different for the A and I transitions: A heavier hole effective mass is reported in Ref. [26] at (m h = 2.45m 0 , m 0 is the electron mass in vacuum) compared to K (m h K = 0.48m 0 ) that results in a difference between the indirect and direct exciton binding energy [47] equal to +144 meV [48]. In turn, this brings our 130 meV exciton value to a 274 meV electronic value, in close agreement with the other works' reported in Table I.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…lectrostatic screening by conducting gates has previously been employed to suppress charge inhomogeneity in graphene [1][2][3] , alter its plasmon spectra 4,5 , and renormalize electronic spectra of monolayer semiconductors 6,7 . Elementary electrostatics tells us that the electron charge e placed at the distance d from a bulk conductor leads to a dipole potential evolving as 2ed 2 =r 3 at large in-plane distances r ) d, which is much weaker than the original, unscreened Coulomb potential, e=r.…”
mentioning
confidence: 99%
“…For instance, given that Coulomb interactions between these charged species are related to dielectric screening, band gap modulation would be proceeded by extrinsically or intrinsically engineering the dielectric properties. 26 , 51 54 In this respect, Raja et al reported band gap modulation of two-dimensional TMDC nanosheets by tuning the surrounding dielectric environment. 52 They constructed heterojunctions between TMDCs and graphene/h-BN nanosheets for achieving dielectric environment regulation.…”
Section: Regulation Of Photosynthesis-related Propertiesmentioning
confidence: 99%